A Modeling of Multi-Echelon Suppliers’ Chain for Deteriorating Items - Jonas Yu; G.A. Widyadana (Institute of Research and Community Outreach - Petra Christian University, 2011)
Inventory models for a policy of retail pricing and perishable items have been developed in many papers, but very few of the studies incorporate both of these effects. This study integrates the two conditions from a three-echelon supplier’s chain and offers a mathematical modeling for deteriorating inventory system with an optimal joint-cost policy. Exponentially deteriorating items with no shortages is assumed in this study. Two scenarios are considered. Scenario 1 assumed one supplier, one distributor and one retailer occurs at the regular inventory replenishment time, and scenario 2 assumes two suppliers, one distributor and two competitive retailers that to address this issue, we broaden the benchmark setting by letting the independent retailer channel be a duopoly. The mathematical model describes how the integrated approach to decision making can achieve global optimality as compared to independent decision by the suppliers, the distributor, and the retailers. A computer code is developed to derive the optimal solution. Numerical examples and sensitivity analysis are given to validate the results of the system.